Faktor Berhubungan dengan Penerimaan Pembelajaran Dari Rumah diMasa Pandemi Covid-19 Bagi Mahasiswa - Yuanita Ani Susilowati; Yovita Tri Katarina; Elizabeth Ari Setyarini (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2022)
Introduction: Suppressing the fall of sacrifice due to covid-19, the Government has established a policy of learning system from face-to-face in class to online. Aim: Know the factors associated with student admission to online learning during the covid-19 pandemic. Method: The design of the study uses descriptive quanta with a cross-sectional approach, respondents are students of all levels who are willing to fill out questionnaires for as many as 190 people, data analysis uses frequency distribution and linear regression through modeling. Results: Showing a relationship between the perception of usefulness and acceptance there is a relationship between the perception of ease and the acceptance of students feeling happy using online learning methods, in behavioral intentions items obtained, which means students want to use the learning process online. Conclusion: Online learning is acceptable and endeared to most students. Recommendations, it is necessary to conduct further studies related to the practice learning process during the pandemic